2017
DOI: 10.12943/cnr.2017.00003
|View full text |Cite
|
Sign up to set email alerts
|

General Assessment of Convection Heat Transfer Correlations for Multiple Geometries and Fluids at Supercritical Pressure

Abstract: Nomenclature c p specific heat capacity at constant pressure (J kg

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…In contrast to that study, the present work separated the HTD data from the entire tube database, and assessed all tube correlations against normal and deteriorated heat transfer (DHT) databases separately. The study by Zahlan et al [4] also revealed that some of the applied CO 2 correlations approximated experimental water data closer than most of the investigated water data-based correlations and vice versa. In addition, some correlations, originally developed for NHT, approximated well the entire database.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…In contrast to that study, the present work separated the HTD data from the entire tube database, and assessed all tube correlations against normal and deteriorated heat transfer (DHT) databases separately. The study by Zahlan et al [4] also revealed that some of the applied CO 2 correlations approximated experimental water data closer than most of the investigated water data-based correlations and vice versa. In addition, some correlations, originally developed for NHT, approximated well the entire database.…”
Section: Introductionmentioning
confidence: 84%
“…In addition to water and CO 2 , the databank comprises measurements collected with refrigerants and helium for round tubes, annuli, and rod bundle subassemblies. Zahlan et al [4] reported a description of the CNL databank compiled prior to 2016 and showed ranges of flow conditions of the databases.…”
Section: Cnl Databank Of Scht and Assessed Correlationsmentioning
confidence: 99%
See 3 more Smart Citations